A comparative study between ionic liquid and acidic pretreatment of waste cotton textiles with simultaneous saccharification and fermentation - Arshi, SS; Zhao, Y; Seyen, TT; Vreckem, EV; Buelens, L (Bangladesh Journal of Scientific and Industrial Research, 2022)
Millions of tons of waste cotton textiles are discarded every year while they could have been used for the production of bioethanol as an alternative for fossil fuel. In this study, the potential of cotton as raw material for ethanol production using ionic liquid (IL) pretreatment and acidic pretreatment is examined and compared, along with non-pretreated cotton samples. The study also aims to determine the optimal temperature of ionic liquid pretreatment, for which experiments under three temperatures (95°C, 150°C, and 175°C) were carried out. Subsequently, the pretreated cotton samples were converted to bioethanol via simultaneous saccharification and fermentation (SSF). Ethanol yields resulting from different pretreatment methods (also non-pretreatment) were compared. Findings suggest that ionic liquid pretreatment under 175°C gives the highest ethanol yield, proving it to be a competitive alternative to traditional acid pretreatment widely applied in industry, as well as demonstrating the prospective usage of waste cotton textiles as biomass for the production of renewable biofuel. Bangladesh J. Sci. Ind. Res. 57(1), 41-48, 2022